2023
DOI: 10.1002/adsc.202300663
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Cross‐Electrophile Coupling of Aryl Phosphates with Aryl Bromides

Jing‐Ao Ren,
Xue Chen,
Chao Gui
et al.

Abstract: A step‐economical and operationally simple nickel‐catalyzed cross‐electrophile coupling of aryl phosphates with aryl bromides through C−O bond cleavage, which precluded the employment of relatively moisture‐labile and unreadily available organometallics, was developed. The reaction proceeded smoothly in the presence of magnesium turnings and lithium chloride in THF to afford the corresponding biaryls in moderate to good yields with reasonable functionality tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…A possible reaction mechanism is proposed on the basis of the obtained experimental results and previous reports. , As shown in Figure , Ni­(acac) 2 first participates in a magnesium-mediated reduction in the presence of dppp to produce nickel(0) species A . Next, an oxidative addition of aryl fluoride 1 with Ni(0) proceeds to give an arylnickel­(II) intermediate B . , After B undergoes a transmetalation with arylmagnesium compound 2′ , which is formed through the oxidative addition of magnesium into aryl bromide 2 , diarylnickel­(II) intermediate C is formed.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…A possible reaction mechanism is proposed on the basis of the obtained experimental results and previous reports. , As shown in Figure , Ni­(acac) 2 first participates in a magnesium-mediated reduction in the presence of dppp to produce nickel(0) species A . Next, an oxidative addition of aryl fluoride 1 with Ni(0) proceeds to give an arylnickel­(II) intermediate B . , After B undergoes a transmetalation with arylmagnesium compound 2′ , which is formed through the oxidative addition of magnesium into aryl bromide 2 , diarylnickel­(II) intermediate C is formed.…”
mentioning
confidence: 61%
“…Thus, we envisioned that the use of magnesium as a reaction promoter, in combination with a transition metal catalyst, might effect the direct cross-coupling of unactivated aryl fluorides with organohalides. In continuation of our endeavors in developing efficient direct cross-couplings of two different electrophiles and useful organic transformations involving C–F bond functionalization, herein we report a nickel-catalyzed direct cross-coupling of unactivated aryl fluorides with aryl bromides, which proceeds efficiently via C–F bond cleavage in the presence of magnesium in THF to produce the corresponding biaryls in moderate to good yields (Scheme f).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, alkylated pyridine and 1,1’-biphenyl derivatives were also successfully prepared, as evidenced from selected examples 9 – 2b and 9 – 2c . In addition to the aforementioned protocol, Shen [ 60 ] and Sun [ 61 ] demonstrated that the cross-coupling reaction of organophosphates 9 – 3a and 9 – 3b with organobromides 9 – 4 can be conducted under reductive cross-coupling conditions ( Scheme 9 b).…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…Although the hydroxylation of aryl thianthrenium salts have been accomplished by using water as hydroxide source, the reaction should be conducted under photoredox conditions in the presence of Ir and Cu catalysts [ 74 ]. In the continuation of our efforts to develop efficient organic transformations with the use of alternative electrophiles [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ] under mild reaction conditions, herein we report a hydroxylation of aryl sulfonium salts by using acetohydroxamic acid and oxime as hydroxylative agents, which enabled the efficient assembly of hydroxylated arenes in modest-to-good yields with good functional group compatibility ( Scheme 1 d).…”
Section: Introductionmentioning
confidence: 99%